Kecanggihan Teknologi Informasi dan Kemampuan Teknik Pemakai Sistem Informasi Akuntansi pada Kinerja Individu - Aiswarya, I Putu Bagus Diva; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2023)
The aim of the research is to empirically prove the influence of information technology sophistication and the technical abilities of accounting information system users on the individual performance of cooperative employees. This research was conducted at a multi-business cooperative in Denpasar. Data was collected through a survey method with questionnaire techniques. The population in this research is all multi-business cooperatives in Denpasar City. The sampling method used was purposive sampling. The number of respondents was 30 people. The data analysis technique used is multiple linear regression analysis. Based on the analysis results, it was found that the sophistication of information technology has a positive and significant effect on individual performance; The ability of accounting information system users has a positive and significant effect on individual performance. Keywords : Sophistication; Capability; Performance.